MASK NARRATIVES PROMOTED BY ANTI-VACCINATION ACCOUNTS ON INSTAGRAM PRIOR TO THE COVID-19 PANDEMIC - Koltai, Kolina; Grohmann, Iva; Johnson, Devin T.; Rondini, Samantha; Foley, Ella R. (AoIR Selected Papers of Internet Research, 2021)
The COVID-19 pandemic has sparked passionate debate worldwide on matters of public health. A portion of this debate has been dedicated to the efficacy of masks to prevent the spread of COVID-19. While the majority of health officials agree that wearing a mask is efficacious, there has been a widespread movement against masks. The “anti-mask” movement is often characterized for spreading misinformation about masks and for its overlap with the anti-vaccine movement. This paper focuses on the mask sentiments of the anti-vaccination community prior to the COVID-19 pandemic. The goal of this paper is to identify if the anti-vaccination movement held prior beliefs about masks to prevent the spread of respiratory diseases and if those beliefs differ from their mask sentiment today. Through thematic analysis of 44 Instagram posts prior to the onset of the COVID-19 pandemic, we find that online vaccine safety communities have, in the past, regarded mask-wearing as a viable alternative to vaccines. Notably, posts supported the efficacy of mask-wearing while criticizing the mandates to wear masks in healthcare settings. In this paper, we elaborate on these mask narratives, as well as their implications in how the anti-vaccination group had a dramatic shift in mask sentiment during the pandemic.